Ultralong Spin Lifetime in Light Alkali Atom Doped Graphene - Márkus, B. G.; Szirmai, P.; Edelthalhammer, Konstantin; Eckerlein, P.; Hirsch, Andreas; Hauke, Frank; Nemes, N. M.; Chacón-Torres, Julio C.; Náfrádi, B.; Forró, L.; Pichler, T.; Simon, F. (ACS nano, 2020)
Today's great challenges of energy and informational technologies are addressed with a singular compound, Li- and Na-doped few-layer graphene. All that is impossible for graphite (homogeneous and high-level Na doping) and unstable for single-layer graphene works very well for this structure. The transformation of the Raman G line to a Fano line shape and the emergence of strong, metallic-like electron spin resonance (ESR) modes attest the high level of graphene doping in liquid ammonia for both kinds of alkali atoms. The spin-relaxation time in our materials, deduced from the ESR line width, is 6-8 ns, which is comparable to the longest values found in spin-transport experiments on ultrahigh-mobility graphene flakes. This could qualify our material as a promising candidate in spintronics devices. On the other hand, the successful sodium doping, this being a highly abundant metal, could be an encouraging alternative to lithium batteries.
CRIS-Team Scopus Importer:2020-07-10
Keywords: alkali atom doping; electron spin lifetime; electron spin resonance; few-layer graphene; Raman spectroscopy